Impact of the Pensión 65 social program on spending on food, 2017-2018 - Inquilla Mamani, Juan; Calatayud Mendoza, Alfredo Pelayo (Universidad del Pacífico, 2019)
The objective of this article is to estimate the impact of the Pension 65 social program on per capita expenditures on food. The study is based on a quantitative methodological perspective, using the differences-in-differences technique with propensity score matching (DD-PSM). For this purpose, the database of the 2017-2018 National Household Survey (ENAHO) is used, both for the treatment and the control group. The unit of analysis are Peruvian households at the national level that participated in the program for two consecutive years, with 2017 as the baseline. The results obtained indicate that per capita expenditure on food has increased by 15.02% for those households that receive the Pensión 65 program.